2021
DOI: 10.1038/s41419-021-04253-y
|View full text |Cite
|
Sign up to set email alerts
|

CircNPHP4 in monocyte-derived small extracellular vesicles controls heterogeneous adhesion in coronary heart atherosclerotic disease

Abstract: Small extracellular vesicles (sEVs)-derived circular RNAs (circRNAs) could regulate gene expression in recipient cells, and dysregulation of sEVs-derived circRNAs has been implicated in several diseases. However, the expression and function of sEVs-derived circRNAs in coronary heart atherosclerotic disease (CAD) remain unknown. In this study, we investigated global changes in the expression patterns of circRNAs in sEVs from CAD-related monocytes and identified circNPHP4 as a significantly upregulated circRNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…EXs containing miR‐106a from ox‐LDL‐exposed macrophages increased proliferation and repressed apoptosis in human SMCs (Liu, Zhang et al., 2020). Monocyte‐derived EVs containing circNPHP4 promoted heterogeneous adhesion between monocytes and coronary artery endothelial cells by sponging miR‐1231 and its target gene, epidermal growth factor receptor, in coronary atherosclerosis (Xiong et al., 2021). EXs containing lncRNA GAS5 from the human monocytic cell line THP‐1 play a role in atherogenesis by dysregulating macrophage and endothelial cell communication (Chen et al., 2017) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…EXs containing miR‐106a from ox‐LDL‐exposed macrophages increased proliferation and repressed apoptosis in human SMCs (Liu, Zhang et al., 2020). Monocyte‐derived EVs containing circNPHP4 promoted heterogeneous adhesion between monocytes and coronary artery endothelial cells by sponging miR‐1231 and its target gene, epidermal growth factor receptor, in coronary atherosclerosis (Xiong et al., 2021). EXs containing lncRNA GAS5 from the human monocytic cell line THP‐1 play a role in atherogenesis by dysregulating macrophage and endothelial cell communication (Chen et al., 2017) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous miRNAs were found to be increased in the circulation of patients with CVDs, namely miR‐1 and miR‐133a, associated with the presence of myocardial damage (Kuwabara et al., 2011). More recently, the circular RNA (circRNA) circNPHP4 was found to be upregulated in monocyte‐derived EVs from CAD patients, being correlated with its clinicopathological status (Xiong et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…First, we extracted monocytes from plasma, and the result of analysis of monocytes can refer to Supplementary Figure S1 of our published article ( 10 ). Through transmission electron microscopy (TEM), we found that the sEVs were ~100 nm in diameter and conformed to the known shape of sEVs.…”
Section: Resultsmentioning
confidence: 99%